Pembentukan IPTLTTS (Instalasi Pengelolaan Lumpur Tinja Terpadu Syariah) di MSAA UIN Maulana Malik Ibrahim Malang - Islam, Ma’riful; Muhari, Muhammad Dheo Adrian; Ardyga, Ibrahim; Al-Haq, Syaif (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
UIN Maulana Malik Ibrahim Malang annually accepts approximately 3,600 new students and is required to enter Ma'had Sunan Ampel Al-'Aly. Having Ma'had is certainly a challenge for the State Islamic University of Maulana Malik Ibrahim Malang in terms of the domestic waste management system for female students, especially wastewater that comes from biological waste such as latrines, in the form of human excrement, and other waste in the form of liquid (black water). . The results of this study show environmental and economic problems with the settlement of 3,600 will produce 1.08 tons of fecal waste with an average breakdown per day each student emits 300 grams of black water waste and multiplied by the number of female students, namely 3,600. The amount of fecal waste produced will cause social, health, environmental and economic problems in the area of ​​UIN Maulana Malik Ibrahim Malang, besides having its own potential if it is managed with a good and correct governance system. The establishment of IPLTTS, which was initiated by researchers, is believed to be a solution to existing environmental and economic problems. This research is a qualitative research with a phenomenological approach and uses library research and field research in collecting data. Keywords: IPLTTS; Dormitory; Feces.